Magnetic polymer-based flexible composite phase change material and preparation method thereof

By modifying the silver plating method of surfaces of polymer substrates and magnetic neodymium iron boron particles, a compact thermal conductivity network is formed, which solves the thermal conductivity and leakage problems of flexible composite phase change materials, and achieves high thermal conductivity and convenient installation of thermal management effects.

CN120365896APending Publication Date: 2025-07-25NANJING TECH UNIV

Patent Information

Application Number
CN202510545706.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The thermal conductivity network structure of existing flexible composite phase change materials is loose and the thermal conductivity direction is inconsistent, resulting in poor thermal management effect and large leakage and contact thermal resistance.

Method used

A composite phase change material emulsion was prepared by mixing carbon nanotube modified polydimethylsiloxane prepolymer with No. 42 paraffin and nanocellulose, and silver was plated on the surface of magnetic neodymium iron boron particles through silver mirror reaction. A compact thermal conductivity network was formed using a magnetic field to eliminate internal voids and ensure saturated filling between components.

Benefits of technology

The prepared magnetic polymer-based flexible composite phase change material has high flexibility and convenient installation at normal temperature, with a thermal conductivity higher than 1.39 W/(m·K), reducing contact thermal resistance, meeting the application needs of phase change thermal management, and preventing leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120365896A_ABST
    Figure CN120365896A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal management material preparation, solves the technical problems of loose heat conduction network structure and non-uniform heat conduction direction of a flexible composite phase change material, and particularly relates to a magnetic polymer-based flexible composite phase change material and a preparation method thereof. Comprising the following steps: preparing a modified polydimethylsiloxane prepolymer from a carbon nanotube dispersion liquid and a polydimethylsiloxane prepolymer; adopting a Pickering emulsion method to mix 42 # paraffin, the modified polydimethylsiloxane prepolymer and nano cellulose to prepare a composite phase change material emulsion; silver mirror reaction is adopted to carry out surface silver plating on the magnetic neodymium iron boron particles; the magnetic polymer-based flexible composite phase change material is prepared from the composite phase change material emulsion and the surface-silvered magnetic neodymium iron boron particles. The high flexibility and magnetism of the prepared material in a normal temperature state endow the material with a more convenient installation mode and lower contact thermal resistance, the heat conduction network structure and component compatibility of the material are improved, and the application requirements of a phase change thermal management technology can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal management material preparation, and particularly to a magnetic polymer-based flexible composite phase change material and a preparation method thereof. Background Art

[0002] The miniaturization and integration of electronic products have led to a sharp increase in their power density, making it extremely easy to form a high-temperature environment inside, which affects the lifespan and reliability of the electronic devices themselves and poses a huge challenge to the thermal management of the devices. Moreover, for some large integrated devices, such as industrial manufacturing equipment, new energy vehicles, etc., as well as devices applied in the aerospace or military fields and often operating under extreme working conditions, they also need to meet complex thermal management requirements from a microscopic scale to a macroscopic scale.

[0003] The phase change thermal management technology is an effective thermal management technology for high-power devices. The phase change material can absorb or release a large amount of heat during the melting or solidification process while the temperature remains almost constant, achieving a good thermal energy control effect. Phase change thermal management belongs to energy storage-type passive temperature control, and its heat dissipation ability mainly depends on the thermal physical properties of the material itself and is almost not restricted by the ambient temperature. At the same time, the phase change thermal management system has the advantages of small volume, light weight, no energy consumption, no moving parts, etc., and has great application value, but there are also problems such as easy leakage, supercooling, low thermal conductivity, and large contact thermal resistance. The flexible composite phase change material based on polymer can confine the phase change material in the flexible polymer matrix to overcome the problems of leakage and large contact thermal resistance of the phase change material. By adding high thermal conductivity fillers, the thermal conductivity of the material is improved, and at the same time, the efficiency of storing and releasing thermal energy of the phase change material is also improved, realizing the stability and durability of the phase change thermal management process.

[0004] In recent years, a large number of literature reports and patent disclosures have been made on flexible composite phase change materials and their preparation processes. However, problems have also arisen in the process of preparing and applying flexible composite phase change materials. The improvement of the thermal conductivity of the material highly depends on the content of the thermal conductivity fillers. By mixing a large amount of thermal conductivity fillers with the other components of the material, the passively formed thermal conduction network is relatively loose and tortuous, affecting the thermal diffusion direction and rate. In addition, although it is effective to relieve the extremely poor compatibility between the material components by means of stirring, ultrasonic waves, etc., due to the relatively high surface tension of the phase change material itself, it is extremely easy to form voids inside the finished material. Therefore, it is necessary to improve it to enhance the thermal management performance of the material.

[0005] As the publication number is CN116716083A and the invention title is a flexible phase change material with a dual-network encapsulation and its three-step hybrid room-temperature pressing method. In this method, expanded graphite and polyoxyethylene octyl phenyl ether are encapsulated within a sodium polyacrylate network structure, and the thermal conductivity of the resulting product is 4.62 W / (m·K). The publication number is CN116640454A and the invention title is a flame-retardant phase change composite material and its preparation method, a flame-retardant flexible phase change material heat-shrinkable film, and a battery module. The phase change material includes paraffin and eicosane, the polymer matrix selects silicone rubber, and expanded graphite is used as a thermal conductive and flame-retardant filler, with a thermal conductivity of about 1.8 W / (m·K). Although the thermal conductivities of these two applications are relatively high, the finished materials obtained only through physical mixing will inevitably have air pores generated due to stirring and mixing remaining inside, which affect heat conduction, and the loose thermal conductive network cannot meet the technical requirements of controllable phase change thermal management. Summary of the Invention

[0006] Aiming at the deficiencies of the prior art, the present invention provides a magnetically attracted polymer-based flexible composite phase change material and its preparation method, which relates to a flexible high-thermal-conductivity and compact composite phase change energy storage material with a phase change temperature of about 42°C and its preparation process, and improves its thermal conductive network structure and component compatibility, which can meet the application requirements of phase change thermal management technology. It solves the technical problems of the loose thermal conductive network structure and non-uniform heat conduction direction of the flexible composite phase change material.

[0007] To solve the above technical problems, the present invention provides the following technical solutions: A preparation method of a magnetically attracted polymer-based flexible composite phase change material, which method comprises the following steps: Prepare a modified polydimethylsiloxane prepolymer using a carbon nanotube dispersion liquid and a polydimethylsiloxane prepolymer; Prepare a composite phase change material emulsion by mixing paraffin No. 42, the modified polydimethylsiloxane prepolymer, and nanocellulose using the Pickering emulsion method; Perform a silver mirror reaction on magnetic neodymium iron boron particles for surface silver plating to obtain surface silver-plated magnetic neodymium iron boron particles; Prepare a magnetically attracted polymer-based flexible composite phase change material using the composite phase change material emulsion and the surface silver-plated magnetic neodymium iron boron particles.

[0008] Further, the preparation of the modified polymer substrate prepolymer includes: Mix carbon nanotubes and deionized water in proportion, then add a dispersant, and obtain a carbon nanotube dispersion liquid through ultrasonic oscillation; Add a polydimethylsiloxane prepolymer and a non-ionic emulsifier to the carbon nanotube dispersion liquid and mix evenly, and use a magnetic stirrer to stir to form a W / O emulsion, that is, a modified polydimethylsiloxane prepolymer.

[0009] Further, the mixing ratio of the carbon nanotubes to deionized water is 2:8; The dispersant includes sodium styrene - maleic anhydride, polyvinyl alcohol, polyvinylpyrrolidone, gelatin, sodium dodecyl sulfate, sodium alginate, and sesquisiloxane; The mass ratio of the carbon nanotube dispersion to the polydimethylsiloxane prepolymer is 1:9 - 3:7; The non - ionic emulsifier includes Span80, Span60, Tween80, Tween60, polyvinyl alcohol solution, gelatin solution, or xanthan gum solution; The mass of the non - ionic emulsifier is 3% - 8% of the mass of the carbon nanotube dispersion; The frequency and time of the ultrasonic oscillation are 50 - 80 Hz and 60 - 90 min respectively, and the temperature, rotation speed, and time of the magnetic stirrer for stirring are 30 - 40 °C, 1000 - 1500 rpm / min, and 30 - 60 min respectively.

[0010] Further, the preparation of the composite phase - change material emulsion includes: At a set temperature, heat paraffin wax No. 42 until it is completely melted, then add the modified polydimethylsiloxane prepolymer and nanocellulose, mix and stir until completely mixed to obtain the composite phase - change material emulsion; The mass ratio of paraffin wax No. 42 to the modified polydimethylsiloxane prepolymer is 2:8 - 4:6, and the mass of nanocellulose is 5% - 10% of the mass of paraffin wax No. 42; The temperature, rotation speed, and duration of the mixing and stirring are 60 - 70 °C, 300 - 600 rpm / min, and 30 - 60 min respectively.

[0011] Further, the surface silver - plating of the magnetic neodymium - iron - boron particles includes: Mix the magnetic neodymium - iron - boron particles and absolute ethanol, and use ultrasonic oscillation to wash the magnetic neodymium - iron - boron particles to remove the impurities on the surface of the magnetic neodymium - iron - boron particles; Add polyvinylpyrrolidone and distilled water, and ultrasonically oscillate again until completely dispersed to obtain a magnetic neodymium - iron - boron particle dispersion; Then add stannous chloride solution to the magnetic neodymium - iron - boron particle dispersion for activation, and then add silver ammonia solution and a reducing agent, and start the silver mirror reaction by magnetic stirring and water - bath heating; Finally, repeat the processes of filtration, washing, and drying to obtain the surface - silver - plated magnetic neodymium - iron - boron particles.

[0012] Further, the concentration of the stannous chloride solution is 0.5 wt% - 1 wt%; The mass ratio of the reducing agent solution used in the silver mirror reaction to the magnetic NdFeB particle dispersion is 10 wt% to 30 wt%, and the reducing agent includes glucose solution, formaldehyde solution, and acetaldehyde solution, until the reaction is completed; The temperature of the silver mirror reaction is controlled at 70-90°C, and the reaction time is 5-10 minutes; During the washing process, distilled water is used to wash away the silver ammonia solution remaining on the surface; during the drying process, the drying temperature is controlled at 50-80° C. and the drying time is 2-3 hours.

[0013] Furthermore, the preparation of the magnetically attractive polymer-based flexible composite phase change material comprises: The composite phase change material emulsion and the surface silver-plated magnetic NdFeB particles are heated and stirred for the first time until they are completely mixed to obtain an uncured magnetically attracted polymer-based flexible composite phase change material, and then a polydimethylsiloxane curing agent is added, and the mixture is heated and stirred again until they are fully mixed; Finally, after ultrasonic, magnetizing and drying processes, a magnetic polymer-based flexible composite phase change material is obtained.

[0014] Furthermore, the temperature, rotation speed and duration of the initial heating and stirring are 60-70°C, 300-600 rpm / min and 20-30 min respectively; the temperature, rotation speed and duration of the second heating and stirring are 50-60°C, 200-400 rpm / min and 5-10 min respectively.

[0015] Furthermore, during the ultrasonic process, the temperature and duration of the ultrasonic oscillation are 50-60° C. and 15-25 min, respectively; During the magnetization process, the uncured magnetically attracted polymer-based flexible composite phase change material is first transferred to the mold, and then the mold is completely placed in a unipolar adjustable air gap electromagnet with a magnetic field strength of 0.8 to 1.6 T; During the drying process, the drying temperature is controlled at 50-60° C. and the drying time is 4.5-6.5 hours.

[0016] The magnetically attractive polymer-based flexible composite phase change material prepared by the above technical scheme uses No. 42 paraffin as the phase change material; polydimethylsiloxane is used as the flexible matrix material, and the matrix material contains carbon nanotube modified material to improve the interfacial heat transfer performance of polydimethylsiloxane; magnetic neodymium iron boron particles are selected as thermal conductive fillers, and silver is plated on the surface to improve the thermal conductivity of the material. Through the magnetic field, the internal gaps of the composite material are eliminated, and the saturated filling between the components is maintained, forming a thermal conductive network with a compact structure and a uniform heat diffusion direction.

[0017] Obtained by the above preparation method, a magnetic polymer-based flexible composite phase change material using paraffin No. 42 as the phase change material, polydimethylsiloxane as the flexible matrix material, and silver-plated magnetic neodymium iron boron particles as the thermal conductive filler. The high flexibility and magnetism of this material at room temperature endow it with a more convenient installation method and lower contact thermal resistance.

[0018] With the above technical solution, the present invention provides a magnetic polymer-based flexible composite phase change material and its preparation method, which at least have the following beneficial effects: 1. The present invention solves the problems of loose thermal conduction network structure and inconsistent thermal conduction direction of the flexible composite phase change material. At the same time, the high flexibility and magnetism of this material at room temperature endow it with a more convenient installation method and lower contact thermal resistance, improving its thermal conduction network structure and component compatibility, and meeting the application requirements of phase change thermal management technology.

[0019] 2. The present invention uses paraffin as the phase change material, and the phase change temperature is within the suitable temperature range of most electronic devices, meeting the requirements of phase change thermal management. The melting enthalpy of the prepared magnetic polymer-based flexible composite phase change material is higher than 62.71 J / g, and the thermal conductivity is higher than 1.39 W / (m·K), having an ideal thermal management effect.

[0020] 3. The present invention uses polydimethylsiloxane as the flexible polymer matrix material, which can achieve high flexibility at room temperature, is convenient for installation and reduces the contact thermal resistance. In addition, high thermal conductivity carbon nanotubes are added to modify the polydimethylsiloxane prepolymer, improving the thermal conductivity of the flexible polymer matrix.

[0021] 4. The present invention uses magnetic neodymium iron boron particles as the thermal conductive filler, and a layer of metallic silver is coated on the surface of the magnetic neodymium iron boron particles by the silver mirror reaction. Due to the excellent thermal conductivity and compactness of silver, the interfacial thermal resistance between the components of the material can be significantly reduced.

[0022] 5. The present invention applies a unipolar magnetic field to the uncured composite material, so that the magnetic neodymium iron boron particles inside the material aggregate to form a three-dimensional magnetic cluster structure with abundant intergranular pores. This structure can remain intact after the magnetic field is removed. Under the capillary action, the remaining liquid component materials fill the internal micropores, form a liquid bridge and are stabilized inside the magnetic cluster, achieving the purpose of preventing leakage.

[0023] 6. The magnetic neodymium iron boron particles of the present invention are arranged along the magnetic field direction to construct an oriented thermal conduction network structure with a unified direction, ensuring the saturated filling between the magnetic neodymium iron boron particles and the other components of the material, and eliminating the problems of incomplete filling and non-tight contact commonly existing in the flexible composite phase change material. Description of the Drawings

[0024] The accompanying drawings described herein are used to provide a further understanding of the present application, and constitute a part of the present application. The schematic embodiments and descriptions thereof of the present application are used to explain the present application, and do not constitute an improper limitation of the present application. In the drawings: Figure 1 It is the macroscopic morphology diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention; Figure 2 It is the microscopic morphology diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention; Figure 3 It is the structure diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention; Figure 4 It is the hysteresis loop curve diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention; Figure 5 It is the magnetic adsorption diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention; Figure 6 It is the DSC curve diagram of the magnetic adsorption type polymer-based flexible composite phase change material of the present invention. Detailed implementation manners

[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation manners. Thereby, the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0026] Although the steps in the present invention are arranged with reference numerals, they are not used to limit the order of the steps. Unless the order of the steps is clearly stated or the execution of a certain step requires other steps as a basis, the relative order of the steps can be adjusted. It can be understood that the term "and / or" used herein refers to and encompasses any and all possible combinations of one or more of the related listed items. Example 1

[0027] The method for preparing the magnetic adsorption type polymer-based flexible composite phase change material proposed in this Example 1 includes the following steps: Step 1: Preparation of modified polymer substrate: Mix 2 parts of carbon nanotubes and 8 parts of deionized water, then add 0.7 part of silsesquioxane, and obtain a carbon nanotube dispersion by ultrasonic oscillation. The ultrasonic frequency is 80 Hz; Mix 1 part of the carbon nanotube dispersion with 9 parts of polydimethylsiloxane prepolymer, then add 0.4 part of Span80 and 0.1 part of Tween80, and use a magnetic stirrer to stir to form a W / O emulsion. The rotation speed is 1200 rpm / min to obtain a modified polydimethylsiloxane prepolymer.

[0028] Step 2: Preparation of composite phase change material emulsion: Take 2 parts of paraffin wax No. 42 and heat it in a water bath until it melts completely. Then add 8 parts of the modified polydimethylsiloxane prepolymer obtained in Step 1 and 0.3 part of nanocellulose, and heat and stir under the condition of a water bath at 60 °C with a stirring speed of 600 rpm / min to obtain the composite phase change material emulsion.

[0029] Step 3: Mix magnetic NdFeB particles with absolute ethanol, and use ultrasonic oscillation to wash the magnetic NdFeB particles to remove impurities on the surface of the magnetic NdFeB particles. The ultrasonic frequency is 50 Hz. Take 3 parts of the washed magnetic NdFeB particles, 5 parts of polyvinylpyrrolidone and 20 parts of distilled water, and ultrasonically oscillate again until completely dispersed to obtain a magnetic NdFeB particle dispersion; Add 0.5 wt% stannous chloride solution to the obtained magnetic NdFeB particle dispersion and mix, ultrasonically oscillate until the magnetic NdFeB particles are completely dispersed, and filter to obtain surface-activated magnetic NdFeB particles. Take 10 parts of 0.1 mol / L silver nitrate solution, dropwise add 5% dilute ammonia water until the generated precipitate completely dissolves, then dropwise add 10 parts of formaldehyde aqueous solution, mix with the surface-activated magnetic NdFeB particles, and heat in a water bath at 60 °C for 10 min. Finally, filter, wash with distilled water, and dry in an 80 °C drying oven for 2 h to obtain surface silver-plated magnetic NdFeB particles.

[0030] Step 4: Take 7 parts of the composite phase change material emulsion obtained in Step 2 and 3 parts of the surface silver-plated magnetic NdFeB particles obtained in Step 3, heat and stir under the condition of a water bath at 60 °C for 30 min, then add 1.4 parts of polydimethylsiloxane curing agent, heat and stir under the condition of a water bath at 50 °C for 5 min to obtain an uncured magnetic polymer-based flexible composite phase change material, and place it in a mold. Under the condition of a water bath at 60 °C, ultrasonically oscillate for 15 min. Place the mold completely inside the magnetic field of a unipolar electromagnet with an air gap height of 16 mm and a magnetic field strength of 1.6 T. Finally, dry in a 55 °C drying oven for 6 h to obtain the magnetic polymer-based flexible composite phase change material. Example 2

[0031] The method for preparing a magnetic polymer-based flexible composite phase change material proposed in this Example 2 includes the following steps: Step 1: Preparation of modified polymer substrate: Mix 2 parts of carbon nanotubes and 8 parts of deionized water, then add 0.7 part of sesquisiloxane, and use ultrasonic oscillation to obtain a carbon nanotube dispersion with an ultrasonic frequency of 80 Hz; Mix 2 parts of the carbon nanotube dispersion with 8 parts of polydimethylsiloxane prepolymer, then add 0.8 part of Span80 and 0.2 part of Tween80, and use a magnetic stirrer to stir to form a W / O emulsion at a rotation speed of 1200 rpm / min to obtain a modified polydimethylsiloxane prepolymer.

[0032] Step 2: Preparation of composite phase change material emulsion: Take 3 parts of paraffin wax No. 42 and heat it in a water bath until it melts completely. Then add 7 parts of the modified polydimethylsiloxane prepolymer obtained in Step 1 and 0.45 part of nanocellulose, and heat and stir under the condition of a water bath at 60 °C with a stirring speed of 600 rpm / min to obtain the composite phase change material emulsion.

[0033] Step 3: Mix magnetic neodymium iron boron particles with absolute ethanol, and use ultrasonic oscillation to wash the magnetic neodymium iron boron particles to remove impurities on the surface of the magnetic neodymium iron boron particles, with an ultrasonic frequency of 50 Hz. Take 3 parts of the washed magnetic neodymium iron boron particles, 5 parts of polyvinylpyrrolidone and 20 parts of distilled water, and ultrasonically oscillate again until completely dispersed to obtain a magnetic neodymium iron boron particle dispersion; Add 0.5 wt% stannous chloride solution to the obtained magnetic neodymium iron boron particle dispersion and mix, ultrasonically oscillate until the magnetic neodymium iron boron particles are completely dispersed, and filter to obtain surface-activated magnetic neodymium iron boron particles. Take 10 parts of 0.1 mol / L silver nitrate solution, dropwise add 5% dilute ammonia water until the generated precipitate completely dissolves, then dropwise add 10 parts of formaldehyde aqueous solution, mix with the surface-activated magnetic neodymium iron boron particles, and heat in a water bath at 60 °C for 10 min. Finally, filter, wash with distilled water, and dry in an 80 °C drying oven for 2 h to obtain surface silver-plated magnetic neodymium iron boron particles.

[0034] Step 4: Take 7 parts of the composite phase change material emulsion obtained in Step 2 and 3 parts of the surface silver-plated magnetic neodymium iron boron particles obtained in Step 3, heat and stir at 60 °C in a water bath for 30 min, then add 1.4 parts of polydimethylsiloxane curing agent, heat and stir at 50 °C in a water bath for 5 min to obtain an uncured magnetic adsorption type polymer-based flexible composite phase change material, and place it in a mold. Under the condition of a water bath at 60 °C, ultrasonically oscillate for 15 min. Place the mold completely inside the magnetic field of a unipolar electromagnet with an air gap height of 16 mm and a magnetic field strength of 1.6 T. Finally, dry in a 55 °C drying oven for 6 h to obtain the magnetic adsorption type polymer-based flexible composite phase change material. Example 3

[0035] The method for preparing a magnetic adsorption type polymer-based flexible composite phase change material proposed in this Example 3 includes the following steps: Step 1: Preparation of modified polymer substrate: Mix 2 parts of carbon nanotubes and 8 parts of deionized water, then add 0.7 part of silsesquioxane, and use ultrasonic oscillation to obtain a carbon nanotube dispersion with an ultrasonic frequency of 80 Hz; Mix 2 parts of the carbon nanotube dispersion with 8 parts of polydimethylsiloxane prepolymer, then add 0.8 part of Span80 and 0.2 part of Tween80, and use a magnetic stirrer to stir to form a W / O emulsion with a rotation speed of 1200 rpm / min to obtain a modified polydimethylsiloxane prepolymer.

[0036] Step 2: Preparation of composite phase change material emulsion: Take 4 parts of paraffin wax No. 42 and heat it in a water bath until it melts completely. Then add 7 parts of the modified polydimethylsiloxane prepolymer obtained in Step 1 and 0.6 part of nanocellulose, and heat and stir under the condition of a water bath at 60 °C with a stirring speed of 600 rpm / min to obtain the composite phase change material emulsion.

[0037] Step 3: Mix magnetic neodymium iron boron particles with absolute ethanol, and use ultrasonic oscillation to wash the magnetic neodymium iron boron particles to remove impurities on the surface of the magnetic neodymium iron boron particles, with an ultrasonic frequency of 50 Hz. Take 3 parts of the washed magnetic neodymium iron boron particles, 5 parts of polyvinylpyrrolidone and 20 parts of distilled water, and ultrasonically oscillate again until completely dispersed to obtain a magnetic neodymium iron boron particle dispersion; Add 0.5 wt% stannous chloride solution to the obtained magnetic neodymium iron boron particle dispersion and mix, and ultrasonically oscillate until the magnetic neodymium iron boron particles are completely dispersed. After filtration, surface-activated magnetic neodymium iron boron particles are obtained. Take 10 parts of 0.1 mol / L silver nitrate solution, dropwise add dilute ammonia water with a concentration of 5% until the generated precipitate completely dissolves, and then dropwise add 10 parts of formaldehyde aqueous solution, mix with the surface-activated magnetic neodymium iron boron particles, and heat in a water bath at 60 °C for 10 min. Finally, filter, wash with distilled water, and dry in a drying oven at 80 °C for 2 h to obtain surface-silver-plated magnetic neodymium iron boron particles.

[0038] Step 4: Take 7 parts of the composite phase change material emulsion obtained in Step 2 and 4 parts of the surface-silver-plated magnetic neodymium iron boron particles obtained in Step 3, heat and stir at 60 °C in a water bath for 30 min, then add 1.4 parts of polydimethylsiloxane curing agent, and heat and stir at 50 °C in a water bath for 5 min to obtain an uncured magnetic adsorption type polymer-based flexible composite phase change material, and place it in a mold. Under the condition of a water bath at 60 °C, ultrasonically oscillate for 15 min. Place the mold completely inside the magnetic field of a unipolar electromagnet with an air gap height of 16 mm and a magnetic field strength of 1.6 T. Finally, dry in a drying oven at 55 °C for 6 h to obtain the magnetic adsorption type polymer-based flexible composite phase change material. Example 4

[0039] The method for preparing a magnetic adsorption type polymer-based flexible composite phase change material proposed in this Example 4 includes the following steps: Step 1: Preparation of modified polymer substrate: Mix 2 parts of carbon nanotubes and 8 parts of deionized water, then add 0.7 part of silsesquioxane, and use ultrasonic oscillation to obtain a carbon nanotube dispersion with an ultrasonic frequency of 80 Hz; Mix 2 parts of the carbon nanotube dispersion with 8 parts of the polydimethylsiloxane prepolymer, then add 0.8 part of Span80 and 0.2 part of Tween80, and use a magnetic stirrer to stir to form a W / O emulsion at a rotation speed of 1200 rpm / min to obtain a modified polydimethylsiloxane prepolymer.

[0040] Step 2: Preparation of the composite phase change material emulsion: Take 4 parts of paraffin wax No. 42 and heat it in a water bath until it is completely melted, then add 7 parts of the modified polydimethylsiloxane prepolymer obtained in Step 1 and 0.6 part of nanocellulose, and heat and stir under the condition of a water bath at 60 °C with a stirring speed of 600 rpm / min to obtain a composite phase change material emulsion.

[0041] Step 3: Mix the magnetic neodymium iron boron particles with absolute ethanol, and use ultrasonic oscillation to wash the magnetic neodymium iron boron particles to remove the impurities on the surface of the magnetic neodymium iron boron particles, with an ultrasonic frequency of 50 Hz. Take 3 parts of the washed magnetic neodymium iron boron particles, 5 parts of polyvinylpyrrolidone, and 20 parts of distilled water, and ultrasonically oscillate again until they are completely dispersed to obtain a magnetic neodymium iron boron particle dispersion; Add a 0.5 wt% stannous chloride solution to the obtained magnetic neodymium iron boron particle dispersion and mix, ultrasonically oscillate until the magnetic neodymium iron boron particles are completely dispersed, and filter to obtain surface-activated magnetic neodymium iron boron particles. Take 10 parts of a 0.1 mol / L silver nitrate solution, dropwise add a 5% dilute ammonia water until the generated precipitate is completely dissolved, then dropwise add 10 parts of a formaldehyde aqueous solution, mix with the surface-activated magnetic neodymium iron boron particles, and heat in a water bath at 60 °C for 10 min. Finally, filter, wash with distilled water, and dry in an 80 °C drying oven for 2 h to obtain surface-silver-plated magnetic neodymium iron boron particles.

[0042] Step 4: Take 7 parts of the composite phase change material emulsion obtained in Step 2 and 5 parts of the surface-silver-plated magnetic neodymium iron boron particles obtained in Step 3, heat and stir in a water bath at 60 °C for 30 min, then add 1.4 parts of a polydimethylsiloxane curing agent, heat and stir in a water bath at 50 °C for 5 min to obtain an uncured magnetic adsorption type polymer-based flexible composite phase change material, and place it in a mold, and ultrasonically oscillate for 15 min under the condition of a water bath at 60 °C. Place the mold completely inside the magnetic field of a unipolar electromagnet with an air gap height of 16 mm and a magnetic field strength of 1.6 T. Finally, dry in a 55 °C drying oven for 6 h to obtain a magnetic adsorption type polymer-based flexible composite phase change material.

[0043] As Figures 1-6 shown, they are respectively the macroscopic morphology diagram, microscopic morphology diagram, internal structure diagram, hysteresis loop curve diagram, magnetic adsorption diagram, and DSC curve diagram of the magnetic adsorption type polymer-based flexible composite phase change material in this application, and the performance of the flexible composite phase change material of each example is shown in Table 1.

[0044] Table 1 Performance of the flexible composite phase change material of each example ; According to Figures 1-6 the results shown, and the melting enthalpy of this application shown in Table 1 is higher than 62.57 J / g, and the thermal conductivity is higher than 1.39 W / (m·K). Therefore, the magnetic polymer-based flexible composite phase change material prepared in this application meets the requirements of electronic device thermal management, has an ideal thermal control effect, improves the thermal conductivity of the flexible phase change material, ensures the saturated filling between the components of the material, enhances the anti-leakage property of the composite phase change material, and has magnetism, can be directly magnetically attracted to the surface of the thermal control device, and reduces the contact thermal resistance.

[0045] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, from any point of view, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be regarded as limiting the claimed invention.

[0046] In addition, it should be understood that although this specification is described according to embodiments, not every embodiment only contains an independent technical solution. This narrative way of the specification is only for clarity. Those skilled in the art should regard the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A preparation method of a magnetic adsorption type polymer-based flexible composite phase change material, characterized in that, The method includes the following steps: Prepare a modified polydimethylsiloxane prepolymer using a carbon nanotube dispersion and a polydimethylsiloxane prepolymer; Prepare a composite phase change material emulsion by mixing paraffin wax No. 42, the modified polydimethylsiloxane prepolymer, and nanocellulose using the Pickering emulsion method; Perform surface silver plating on magnetic neodymium iron boron particles through a silver mirror reaction to obtain surface silver-plated magnetic neodymium iron boron particles; Prepare a magnetically attracted polymer-based flexible composite phase change material using the composite phase change material emulsion and the surface silver-plated magnetic neodymium iron boron particles.

2. The preparation method according to claim 1, characterized in that, The preparation of the modified polymer substrate prepolymer includes: Mix carbon nanotubes and deionized water in proportion, then add a dispersant, and obtain a carbon nanotube dispersion through ultrasonic oscillation; Add a polydimethylsiloxane prepolymer and a nonionic emulsifier to the carbon nanotube dispersion and mix evenly, and use a magnetic stirrer to stir to form a W / O emulsion, that is, a modified polydimethylsiloxane prepolymer.

3. The preparation method according to claim 2, characterized in that, The mixing ratio of the carbon nanotubes to the deionized water is 2:8; The dispersant includes sodium styrene-maleic anhydride, polyvinyl alcohol, polyvinylpyrrolidone, gelatin, sodium dodecyl sulfate, sodium alginate, and sesquisiloxane; The mass ratio of the carbon nanotube dispersion to the polydimethylsiloxane prepolymer is 1:9 to 3:7; The nonionic emulsifier includes Span80, Span60, Tween80, Tween60, a polyvinyl alcohol solution, a gelatin solution, or a xanthan gum solution; The mass of the nonionic emulsifier is 3% to 8% of the mass of the carbon nanotube dispersion; The frequency and time of the ultrasonic oscillation are 50 to 80 Hz and 60 to 90 min respectively, and the temperature, rotation speed, and time of the magnetic stirrer for stirring are 30 to 40 °C, 1000 to 1500 rpm / min, and 30 to 60 min respectively.

4. The preparation method according to claim 1, wherein, The preparation of the composite phase change material emulsion includes: At a set temperature, heat paraffin wax No. 42 until it is completely melted, then add the modified polydimethylsiloxane prepolymer and nanocellulose and mix and stir until completely mixed to obtain a composite phase change material emulsion; The mass ratio of paraffin wax No. 42 to the modified polydimethylsiloxane prepolymer is 2:8 to 4:6, and the mass of the nanocellulose is 5% to 10% of the mass of paraffin wax No. 42; The temperature, rotation speed, and duration of the mixing and stirring are 60 to 70 °C, 300 to 600 rpm / min, and 30 to 60 min respectively.

5. The preparation method according to claim 1, wherein The surface silver plating of the magnetic neodymium iron boron particles includes: Mix the magnetic neodymium iron boron particles and absolute ethanol, and use ultrasonic oscillation to wash the magnetic neodymium iron boron particles to remove impurities on the surface of the magnetic neodymium iron boron particles; Add polyvinylpyrrolidone and distilled water, and ultrasonically oscillate again until completely dispersed to obtain a magnetic neodymium iron boron particle dispersion; Then add a stannous chloride solution to the magnetic neodymium iron boron particle dispersion for activation, and then add a silver ammonia solution and a reducing agent, and start the silver mirror reaction by magnetic stirring and water bath heating; Finally, repeat the processes of filtration, washing, and drying to obtain surface silver-plated magnetic neodymium iron boron particles.

6. The preparation method according to claim 5, characterized in that, The concentration of the stannous chloride solution is 0.5 wt% to 1 wt%; The mass ratio of the reducing agent solution used in the silver mirror reaction to the magnetic neodymium iron boron particle dispersion is 10 wt% to 30 wt%. The reducing agent includes glucose solution, formaldehyde solution, and acetaldehyde solution until the reaction is completed; The temperature of the silver mirror reaction is controlled at 70 - 90 °C, and the reaction time is 5 - 10 min; During the washing process, the residual silver ammonia solution on the surface is washed away with distilled water; during the drying process, the drying temperature is controlled at 50 - 80 °C, and the drying time is 2 - 3 h.

7. The preparation method according to claim 1, characterized in that, The preparation of the magnetic polymer-based flexible composite phase change material includes: Taking the composite phase change material emulsion and the surface silver-plated magnetic neodymium iron boron particles, initially heating and stirring until completely mixed to obtain the uncured magnetic polymer-based flexible composite phase change material, and then adding a polydimethylsiloxane curing agent and heating and stirring again until fully mixed; Finally, through ultrasonic treatment, magnetization, and drying processes, the magnetic polymer-based flexible composite phase change material is obtained.

8. The preparation method according to claim 7, characterized in that, The temperature, rotation speed, and duration of the initial heating and stirring are 60 - 70 °C, 300 - 600 rpm / min, and 20 - 30 min respectively; the temperature, rotation speed, and duration of the second heating and stirring are 50 - 60 °C, 200 - 400 rpm / min, and 5 - 10 min respectively.

9. The preparation method according to claim 7, wherein During the ultrasonic treatment process, the temperature and duration of the ultrasonic oscillation are 50 - 60 °C and 15 - 25 min respectively; During the magnetization process, first transfer the uncured magnetic polymer-based flexible composite phase change material to a mold, and then place the mold completely inside a unipolar adjustable air-gap electromagnet with a magnetic field strength of 0.8 - 1.6 T; During the drying process, the drying temperature is controlled at 50 - 60 °C, and the drying time is 4.5 - 6.5 h.

10. A magnetic adsorption type polymer-based flexible composite phase change material, characterized in that, Using the preparation method described in any one of the above claims 1 - 9, a magnetic polymer-based flexible composite phase change material is obtained with paraffin No. 42 as the phase change material, polydimethylsiloxane as the flexible matrix material, and surface silver-plated magnetic neodymium iron boron particles as the thermal conductivity filler.

Citation Information

Patent Citations

  • Flame-retardant phase-change composite material and preparation method thereof, flame-retardant flexible phase-change material heat-shrinkable film and battery module

    CN116640454A

  • Dual-network packaged flexible phase change material and three-step mixing normal-temperature pressing method thereof

    CN116716083A

Cited By

  • Magnetic control phase change efficient heat transfer copper pipe and preparation process thereof

    CN121025844A

  • Magnetic control phase change high-efficiency heat transfer copper pipe and preparation process thereof

    CN121025844B

  • Capacitive flexible pressure sensor based on porous NdFeB-PDMS composite material and preparation method and application thereof

    CN121384275A

  • Multilayer coated flexible phase change material based on post-plating bamboo fibers oriented by magnetic field and preparation method thereof

    CN122705956A